Narratives of Resilience and Resistance in J. M. Coetzee’s Age of Iron (International Journal of Food and Nutritional Sciences, 2022)
J.M. Coetzee, a South African novelist, is renowned for his profound explorations of apartheid, morality, and human suffering. In Age of Iron by J.M. Coetzee, Mrs. Curren, an elderly professor from Cape Town who is battling terminal cancer. She contemplates her existence during the harsh realities of apartheid South Africa. Her relationship with Vercueil, a man without a home, and her dealings with Bheki, a young black activist, shed light on her increasing understanding of racial inequalities. Despite her own hardships and the turmoil around her, Mrs. Curren shows remarkable strength and bravery. She criticizes the violence of apartheid, builds compassionate relationships, and documents her journey through letters, which serve as a form of resistance against oppression. Coetzee delves into the ideas of determination, moral responsibility, and rebellion, showcasing Mrs. Curren’s inner fortitude and her growing support for those on the fringes of society, ultimately highlighting the human spirit’s ability to endure through political and personal challenges. This paper explores personal and political struggles of Mrs. Curren, as she navigates the harsh realities of apartheid South Africa, forging bonds and finding resilience amidst societal unrest.